Evidence of validity and reliability of the controlling motivational style questionnaire in the work context - (:unkn) unknown (Pireo Editorial, 2024)
According to the self-determination theory (SDT), leaders may adopt a controlling motivational controlling style (CMS) that forces employees to think, feel, or behave in a certain way to promote employee motivation. However, a scale has yet to be develop...
Keywords: Motivación laboral; Validez